Effects of selected medium components for production of glucose oxidase by a local isolate Aspergillus terreus UniMAP AA-1 - Ahmad Anas, Nagoor Gunny; Arbain, Dachyar; Muhammad Syarhabil, Ahmad, Dr. (Elsevier B. V., 2012)
Link to publisher's homepage at http://www.elsevier.com